Consequentialism, the Action/Omission Distinction, and the Principle of Double Effect: Three Rival Criteria to Solve Vital Conflicts in Cases of Necessity. (15th November 2017) - Miranda, Alejandro
Abstract: In this paper, the principle of double effect is compared with two other methods to solve vital conflicts in cases of necessity, i.e., situations in which the life of a person can only be saved by an action that causes the death of another. After determining some key concepts, the consequentialist method of moral reasoning is analyzed, and it is shown why it should be rejected by a legal system that recognizes the inviolable dignity of the human person and the absolute rights founded on it. Next the doctrine that gives importance to the distinction between action and omission is examined. The author shows that this doctrine, although it has been subscribed to by some philosophers and jurists, attributes an unjustified moral relevance to physical causality. Finally, an argument is presented to demonstrate that the principle of double effect is the correct doctrine by which resolve vital conflicts in cases of necessity.